Evaluasi Dan Penjamin Mutu: Kunci Keberhasilan Manajemen Pendidikan - Nadia Puteri Alindi; Zadzqia Yuha Rumsah; Hesti Kusumaningrum (PT PUSTAKA CENDEKIA GROUP, 2025)
This article discusses the role of evaluation and quality assurance as key factors in the success of educational management. The main objective of this study is to explain the concept and importance of educational quality, quality assurance systems, as well as the goals and principles of educational quality assurance. The methods used include a literature review and an analysis of existing quality assurance systems. The research findings indicate that effective quality assurance involves the implementation of clear paradigms, principles, and goals. Meanwhile, educational evaluation plays a crucial role in assessing and improving educational quality through its structured characteristics and functions. The study concludes that the integration of a comprehensive assessment and quality assurance system is a critical factor in achieving success in educational management, providing practical guidance for education managers to ensure high standards and ongoing educational improvement.